Technical and Economic Analysis of On-Grid Rooftop Solar PV at the PLN ULP Ampana Office Using Pvsyst Software to Minimize Carbon Emissions - Melati Primandari; Rony Seto Wibowo; Feby Agung Pamuji (Politeknik Siber Cerdika Internasional, 2026)
Background: Rooftop solar power in office buildings supports energy efficiency and the clean energy transition but requires technical, economic, and environmental feasibility assessment. Objective: This study analyzes the technical, economic, and environmental feasibility of on-grid rooftop solar PV at PT PLN (Persero) ULP Ampana, addressing the limited integrated studies on PLN service office buildings. Methods: The research was conducted through the analysis of electrical energy needs, determination of system capacity, selection of modules and inverters, with PVsyst simulation. Economic analysis is carried out using investment feasibility parameters, while environmental analysis estimated reduction of carbon emissions from the system. Results: The results showed that the system was designed with a capacity of 5.0 kWp using Longi Solar LR5-66HPH-500M with a power of 500 Wp and 1 inverter of Growatt MOD 4000TL3-X with a capacity of 4.0 kW. The simulation results show that energy production is 7,840.73 kWh/year, a performance ratio of 76.58%, and a solar fraction of 50.48%. From the economic aspect, the NPV value is IDR 3.451.597 (positive), BCR of 1.04 (above 1), Payback Period of 22.4 years, and IRR of 6.7%. The utilization of this rooftop solar PV system can reduce emissions by 66.85 ton CO₂e over a 25-year period, supporting PLN’s operational efficiency and renewable energy targets. Conclusion: The planning of a grid-connected rooftop solar power system at the PLN ULP Ampana Office is technically, economically, and environmentally feasible, with the potential to serve as a pilot project for solar energy implementation in PLN office buildings.